Synthesis, photophysical and electrochemical properties of pyridine, pyrazine and triazine-based (D–π–)(2)A fluorescent dyes - Imato, Keiichi (Beilstein J Org Chem, 2019)
The donor–acceptor–π-conjugated (D–π–)(2)A fluorescent dyes OUY-2, OUK-2 and OUJ-2 with two (diphenylamino)carbazole thiophene units as D (electron-donating group)–π (π-conjugated bridge) moiety and a pyridine, pyrazine or triazine ring as electron-withdrawing group (electron-accepting group, A) have been designed and synthesized. The photophysical and electrochemical properties of the three dyes were investigated by photoabsorption and fluorescence spectroscopy, Lippert–Mataga plots, cyclic voltammetry and density functional theory calculations. The photoabsorption maximum (λ(max,abs)) and the fluorescence maximum (λ(max,fl)) for the intramolecular charge-transfer characteristic band of the (D–π–)(2)A fluorescent dyes show bathochromic shifts in the order of OUY-2 < OUK-2 < OUJ-2. Moreover, the photoabsorption bands of the (D–π–)(2)A fluorescent dyes are nearly independent of solvent polarity, while the fluorescence bands showed bathochromic shifts with increasing solvent polarity (i.e., positive fluorescence solvatochromism). The Lippert–Mataga plots for OUY-2, OUK-2 and OUJ-2 indicate that the Δμ (= μ(e) − μ(g)) value, which is the difference in the dipole moment of the dye between the excited (μ(e)) and the ground (μ(g)) states, increases in the order of OUY-2 < OUK-2 < OUJ-2. Therefore, the fact explains our findings that OUJ-2 shows large bathochromic shifts of the fluorescence maxima in polar solvents, as well as the Stokes shift values of OUJ-2 in polar solvents are much larger than those in nonpolar solvents. The cyclic voltammetry of OUY-2, OUK-2 and OUJ-2 demonstrated that there is little difference in the HOMO energy level among the three dyes, but the LUMO energy levels decrease in the order of OUY-2 > OUK-2 > OUJ-2. Consequently, this work reveals that for the (D–π–)(2)A fluorescent dyes OUY-2, OUK-2 and OUJ-2 the bathochromic shifts of λ(max,abs) and λ(max,fl) and the lowering of the LUMO energy level are dependent on the electron-withdrawing ability of the azine ring, which increases in the order of OUY-2 < OUK-2 < OUJ-2.